An overview of the Corpus Protagoreum : a bibliographical note on Laks and Most’s Early Greek Philosophy - Barrionuevo, Sergio Javier (2018)
Fil: Barrionuevo, Sergio Javier. Universidad Nacional de General Sarmiento. Instituto de Ciencias; Argentina.